Nikolai Berdiaev and the “boundless spaces” of Russia - Mjør, Kåre Johan (Nordlit, 2017)
The article analyses the ways in which the Russian philosopher Nikolai Berdiaev understood Russian space and geography, beginning with the texts that he wrote during the First World War and ending with his book The Russian Idea (1946). It was characteristic of Berdiaev to extensively recycle passages from his own texts, not least those that put forth the claim that there was a correspondence between Russia’s vast and wide-open spaces and the “Russian soul.” However, the article argues that Berdiaev’s seemingly similar phrases had different meanings in different contexts. In the 1910s, his perspective was predominantly critical, if speculative, positing that the acquisition of large territories had prevented the Russian “self-organization” in thought and culture. After the 1917 revolutions and his own emigration in 1922, by contrast, Berdiaev gradually became more essentialist in his approach to Russian space, seeing the vast territories as perfectly matching the strivings and quests of the Russian people. The article contextualises Berdiaev’s understanding of space both in relation to nineteenth-century traditions of interpreting Russian geography and to the political upheavals that took place during his lifetime.